Depression and socio-economical burden are more common in primary caregivers of patients who are not aware of their cancer: TURQUOISE Study by the Palliative Care Working Committee of the Turkish Oncology Group (TOG) - (:unkn) unknown (WILEY, 2016)
In this study, we aimed to determine the personal, social and economic burden and the frequency of depression, as well as in caregivers of cancer patients who are being treated with chemotherapy in Turkey. The study is designed as a cross-sectional survey study using a 5-point Likert-type response scale, and the last part of the questionnaire includes the Beck Depression Inventory. The depression rate was found to be 64% (n=476) among all subjects (n=968), with 91% of those with depression demonstrating signs of mild depression. In this study, a significant difference was found between the presence of depression and age (young), sex (female), educational level (high), economic status (low), financial loss during treatment, patient's lack of knowledge about his/her diagnosis, metastatic disease and short survival time. In addition, 64% of all subjects had concerns of getting cancer, and 44% of all subjects had feelings of anger/rage against other people. In a multivariate regression analysis, the patient's lack of knowledge of the diagnosis was the independent risk factor. In conclusion, depression incidence and burden rate increased among cancer caregivers, and care burden was highly associated with depression. Accordingly, approaches to reducing the psycho-social effects of cancer should focus intensively on both the patients and their caregivers in Turkey.
Keywords: cancer caregivers; depression; anxiety; social burden; economical burden; QUALITY-OF-LIFE; FAMILY CAREGIVERS; BREAST-CANCER; BRAIN-TUMOR; ANXIETY; HEALTH; PARTNERS; NEEDS; INTERVENTIONS; COMMUNICATION